SPIRITUALITY AND COPING STRATEGY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Nur Widayati; Nuhita Siti Rohmin; Retno Purwandari (UNEJ e-Proceeding, 2020)
Patients with type 2 Diabetes Mellitus (DM) experience changes related to self-care management. This condition can lead to a negative psychological reaction such as stress. People deal with stress depending on their coping strategy. One of the factors affecting coping strategy is spirituality. This study aimed to analyse the correlation between spirituality and coping strategy in type 2 DM patients. This research applied an observational analytic design with cross-sectional approach. A total of 84 respondents were enrolled in this study by using consecutive sampling technique. Data collection was conducted by administering questionnaires of Daily Spiritual Experience Scale (DSES) and Cope Inventory. Data were analysed by using Spearman correlation test with significance level of 0.05. The result showed that the mean value of spirituality was 70.25 and coping strategy was 75.88. There was a significant positive correlation between spirituality and coping strategy (p-value: 0.001; r: 0.616). The correlation is strong and positive which means the higher the level of spirituality the better the coping strategy. This study suggests the importance of assessing the aspect of spirituality to optimize coping strategy in patients with type 2 DM. Keywords: Type 2 Diabetes Mellitus; Spirituality; Coping Strategy